2018
DOI: 10.3390/met8070502
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Deep Cryogenic Treatment on Wear Resistance and Structure of GB 35CrMoV Steel

Abstract: Wear resistance of metallic materials can be effectively improved by the deep cryogenic treatment. In this study, different deep cryogenic treatment conditions were considered, with different soaking durations between quenching and tempering. The main objective is investigating the effects of deep cryogenic treatment and exploring the relationship between the mechanical properties and the microstructure of GB 35CrMoV steel. Hardness and relative wear ratios of samples were evaluated by the Vickers-hardness tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
(33 reference statements)
2
10
0
Order By: Relevance
“…The energy spectrum analysis results of the 35CrMoV steel matrix and corrosion products after corrosion are displayed in Figure 15. It can be seen from Figure 15 that the surface of the matrix after heat treatment mainly contains Fe, and some studies have shown that its structure is tempered sorbite [49,50]. In summary, the corrosion products on the surface after corrosion are mainly FeOOH.…”
Section: Resultsmentioning
confidence: 97%
“…The energy spectrum analysis results of the 35CrMoV steel matrix and corrosion products after corrosion are displayed in Figure 15. It can be seen from Figure 15 that the surface of the matrix after heat treatment mainly contains Fe, and some studies have shown that its structure is tempered sorbite [49,50]. In summary, the corrosion products on the surface after corrosion are mainly FeOOH.…”
Section: Resultsmentioning
confidence: 97%
“…By applying the same strategy Amini et al, [12] detected a lower hardness when investigated tool made as cold work from steel 80CrMo12 5. The higher cryogenic soaking times generate significant improvements in hardness and wear resistance [41].…”
Section: Maximum Contact Temperature ( )mentioning
confidence: 99%
“…11b shows a A3T treated sample and shows laths of martensite, fine globular carbide alongwith retained austenite. process [41]. It is suspected that the CT permits to increase the driving force for the nucleation of carbides and the number of carbides increased while the carbides size was decreased [42].…”
Section: Maximum Contact Temperature ( )mentioning
confidence: 99%
“…Besides this, tool life and wear resistance of the alloys are also significantly enhanced with appropriate cryogenic treatment [30]. In this type of treatment, cooling time, soaking rate and temperature are the critical parameters that alter the properties of alloys [31][32][33]. Researchers have tried to optimize these parameters to achieve the desired material characteristics.…”
Section: Introductionmentioning
confidence: 99%